Carbon dioxide emission in the Middle East and North African (MENA) region : a dynamic panel data study / Siti Ayu Jalil - Jalil, Siti Ayu (Faculty of Business and Management, 2014)
This empirical study investigates the determinants of CO2 emission in 18 countries of the Middle East and North African region covering the period from 1971 to 2009. The analysis is based on a dynamic panel data model employing the Generalized Method of Moments (GMM) technique. The potential determinants of carbon emissions identified are per capita gross domestic product, energy usage, energy consumption from fossil fuel, foreign direct investment, urbanization, industrial production, agricultural production and education level. The results show per capita gross domestic product, energy consumption based on fossil fuel, foreign direct investment and agriculture production have significant impact on the growth of carbon emissions in the region.